Synthesis of glycolipids inspired by Fucus distichus and natural product isolation and characterization of Euphorbia lancifolia - Jewell, Linda Elizabeth (University of Ottawa (Canada), 2009)
The ethanolic extracts of Fucus distichus, a freshwater brown algae harvested from Ungava Bay in northern Quebec, have demonstrated antiviral and antibiotic activity. The major component and potential active molecule from this seaweed was identified as a glycolipid consisting of beta- D-galactose linked to two o-linolenic acid chains via a glycerol unit. The synthesis of this glycolipid, as well as a number of derivatives, is described to investigate their antibiotic and antiviral activity relative to the natural product. One major family of analogues explored includes C-linked glycolipids, where a carbon-carbon linkage replaces the metabolically unstable C-O ester bond between the sugar and the glycerol in the natural product. The natural product, as well as eight other analogues were synthesized. Bioactivity data for some of the compounds is described. In a second project, an investigation into the major constituents of Euphorbia lancifolia (Ixbut) was undertaken. Although there have been no in-depth reported chemical studies of E. lancifolia to date, traditional medicine in Latin America claims that the plant leaves can be used in herbal tea as a galactogogue, a drug which induces lactation. The goal of this study was to identify the major constituents of E. lancifolia as the first step in investigating the claims regarding the plant's biological activity. Nine compounds, including the novel triterpene derivative beta-amyryl ferulate, were identified and isolated. Biological assays testing the ability of these compounds to interact with the metabolism of dopamine, an important hormone in lactation, will be undertaken shortly.
Keywords: Chemistry, Organic.